The Aristotelian Problemata physica : philosophical and scientific investigations - Mayhew, Robert. (Philosophia Antiqua, 2015)
The Problemata physica is the third longest work in the corpus Aristotelicum, but among the least studied. It consists of 38 books, over 900 chapters, covering a vast range of subjects, including medicine and music, sex and salt water, fatigue and fruit, animals and astronomy, moderation and malodorous things, wind and wine, bruises and barley, voice and virtue. Aristotelian Problemata Physica : Philosophical and Scientific Investigations consists of 21 essays by scholars of ancient Greek philosophy and science. These essays shed light on this mysterious work, providing insights into the nature of philosophical and scientific inquiry in the Lyceum during Aristotle's life and especially in the years following his death.